2009
DOI: 10.1021/jf900549c
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Phase II Enzymes by Sulforaphane: Implications for Its Cardioprotective Potential

Abstract: Oxidative stress plays a major role in the pathophysiology of cardiac disorders, but the experimental data on the protective effects of exogenous antioxidants are controversial. A promising cardioprotective strategy may be through the induction of the endogenous antioxidants and phase II enzymes by chemical inducers. Sulforaphane is an isothiocyanate derived from cruciferous vegetables, and it has gained attention mainly as a potential chemopreventive agent in part through the induction of detoxifying enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 39 publications
(45 reference statements)
4
89
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14]20,21 Moreover, SFN from broccoli sprouts has already been evaluated in a phase I clinical trial that demonstrated its good safety profile, 22 and a phase II clinical trial for treating patients with recurrent prostate cancer is currently being performed (ClinicalTrials.gov, NCT01228084).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14]20,21 Moreover, SFN from broccoli sprouts has already been evaluated in a phase I clinical trial that demonstrated its good safety profile, 22 and a phase II clinical trial for treating patients with recurrent prostate cancer is currently being performed (ClinicalTrials.gov, NCT01228084).…”
Section: Discussionmentioning
confidence: 99%
“…8 In particular, SFN anti-tumoral activity is exerted by its different pleiotropic effects that continue to increase and that actually include: suppression of cell cycle progression, induction of apoptosis, inhibition of angiogenesis, 9 antiinflammatory activity, 10 specific modulation of gene expression, epigenetic effects such as the inhibition of histone deacetylases, 11 activation of phase II detoxifying enzymes, and suppression of cytochrome P450 enzymes. 12 In vivo studies in animals have shown that sulforaphane is rapidly absorbed, displays an absolute bioavailability of 82%, and induces a reduction in the frequency, size, and number of many tumors, 13,14 while no side effects have been reported. 14 The activities of SFN may suggest the identification of a rational combination of SFN with other therapeutic molecules that could trigger a potent anti-tumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SFN can prevent 6-hydroxydopamine-induced cytotoxicity in dopaminergic neurons (Han et al, 2007). More recently, studies have found that SFN has cardioprotective effects in neonatal cardiac myocytes by reducing ROS generation and increasing cell viability (Angeloni et al, 2009). Protective effects against postischaemia by SFN have also been reported in kidneys (Yoon et al, 2008), astrocytes (Danilov et al, 2009) and pancreatic islet cells (Solowiej et al, 2004).…”
Section: Figurementioning
confidence: 97%
“…2 Sulforaphane has been described as "the most potent inducer of phase II enzymes identified to date" 7 and has shown benefits in alleviating multiple chronic conditions, including allergic respiratory inflammation from oxidant stimuli in the upper airway caused by asthma or air pollutants. 7 It has also been associated with decreased risk of various cardiovascular diseases, 8 lung cancer, 9 prostate cancer, 10 urinary cancer, 11 and colon cancer. 12 In addition to sulforaphane, other products of myrosinase-induced degradation of glucosinolate have been demonstrated to have significant anticarcinogenic benefits.…”
Section: Introductionmentioning
confidence: 99%